2002
DOI: 10.1212/wnl.58.10.1546
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up of subthalamic nucleus stimulation in Parkinson’s disease

Abstract: Twenty-two patients with PD received bilateral implants for high frequency stimulation of the subthalamic nucleus. The patients were treated for more than 1 year (up to 36 months). At the last visit, the Unified Parkinson Disease Rating Scale (UPDRS) motor score without medication improved by 50.2% (p < 0.001) and the UPDRS activities of daily living score improved by 68.4% (p < 0.001). The most common long-lasting adverse events were hypophonia and dysarthria; transient events were increased sexuality and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
116
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 11 publications
11
116
1
4
Order By: Relevance
“…Among our patients, the duration and disability of LID were reduced by 73% and 77% at 2 years, respectively. The outcomes are comparable to those reported by other investigators (8,17,19,22,23).…”
Section: █ Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Among our patients, the duration and disability of LID were reduced by 73% and 77% at 2 years, respectively. The outcomes are comparable to those reported by other investigators (8,17,19,22,23).…”
Section: █ Discussionsupporting
confidence: 89%
“…Stimulation and levodopa may exacerbate contralateral dyskinesia which necessitates a reduction of the daily levodopa dose, which in turn fails to UPDRS score was 33, which was comparable to preoperative motor UPDRS scores reported by other authors (4,26), although other authors utilized unilateral STN DBS in more advanced PD (22,23). Bilateral STN DBS has been reported to provide a 30 to 60% improvement in the total motor UPDRS score (12,17,20,21,28). In a preliminary study reported by Verhagen in 25 patients with a 4-month follow-up unilateral STN DBS reduced the UPDRS motor score by 31% (24).…”
Section: █ Discussionsupporting
confidence: 65%
See 3 more Smart Citations